A community‐based study of respiratory episodes in Melbourne, Australia - Karin Leder; Martha I. Sinclair; Teresa Z. Mitakaki; Margaret E. Hellard; Andrew Forbes; Christopher K. Fairley (Elsevier, 2003)
Abstract Objective:To provide recent data regarding the epidemiology of community‐based respiratory infections in Australia. Methods:A longitudinal study between 1997-99 involving collection of a health diary from 600 families in Melbourne. Results:More than 80% of study participants reported at least one respiratory episode over 15 months. An average of 2.2 respiratory episodes per person per year w as reported, with a mean episode duration of 6.3 days. On average, subjects were symptomatic for 4.2% of the study days. Compared with other age groups, children aged less than two years were most likely to have at least one respiratory episode, a greater number of episodes per person and the longest episode duration (6.8 days). Approximately one in three (28.7%) respiratory episodes were associated with a doctor's visit, and one in four (23%) necessitated time off school or work. Exposure to other people with respiratory symptoms was commonly reported. Conclusions:Respiratory infections are common, cause a significant amount of morbidity, and are major contributors to the total community health burden. Implications:The direct and indirect costs of respiratory infections to the community are substantial.